Post-Compression of 9.2-µm Terawatt Laser Pulses to Femtoseconds - Pogorelsky Igor V. (EDP Sciences, 2021)
Contemporary CO2 laser systems are capable to delivering picosecond pulses of the multi-terawatt peak power. Further pulse compression to a few cycles is possible using a post-compression in bulk materials with negative group velocity dispersion (GVD). We have experimentally demonstrated the post-compression of a long-wave infrared (9.2 μm) 150-GW peak power pulse from 1.85 ps to less than 500 fs using a combination of two optical materials with significantly different ratios of the nonlinear refractive index to the GVD coefficient. Such combination allows for optimization of the compression mechanism and promises a viable path to scaling peak powers to multi-terawatt levels.